Women, precarious work and care : the failure of family-friendly rights - Grabham, Emily (Bristol : Bristol University Press, 2021)
Drawing on interviews with women in precarious work, this text explores the everyday problems they face balancing work and care responsibilities. This crucial book exposes the failures of family-friendly rights and explains how to grant these women effective rights in the wake of COVID-19.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Women -- Employment; Women's rights; Employee rights; Temporary employment; Part-time employment; Women caregivers